ENGINEERING ACTIVITIES IN MODERN CONDITIONS AGRICULTURAL PRODUCTION - Storozhuk, L.; Chervinsky, L. (Energy and Automation, 2016)
The analysis of industrial and scientific activities of modern engineering, its formation and development; the problems of engineering in solving practical problems in production agriculture.